The 8051 microcontroller and embedded systems : using Assembly and C - Mazidi, Muhammad Ali.; McKinlay, Rolin D. (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2006)
"This textbook covers the hardware and software features of the 8051 in a systematic and step-by-step way."-back cover.
Introduction to computing -- The 8051 microcontrollers -- 8051 assembly language programming -- Jump, loop, and call instructions -- I/O port programming -- 8051 addressing modes -- Arithmetic & logic instructions and programs -- 8051 Programming in C -- 8051 hardware connection and Intel hex file -- 8051 timer programming in assembly and C -- 8051 serial port programming in assembly and C -- Interrupts programming in assembly and C -- LCD and keyboard interfacing -- ADC, DAC, and sensor interfacing -- 8051 Interfacing to external memory -- 8051Interfacing with the 8255 -- DS12887 RTC interfacing and programming -- Motor control : relay, PWM, DC, and stepper motors -- 8051 instructions, timing, and registers -- Basics of wire wrapping -- Technology and system design issues -- Flowcharts and pseudocode -- 8051 primer for X86 programmers -- ASCII codes -- Assemblers, development resources, and suppliers -- Data sheets.
Includes index.
1
Keywords: Programmable controllers; Microcontrollers; Embedded computer systems